PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN MINAT HAFALAN AL-QUR’AN SISWA KELAS VII PADA EKSTRAKULIKULER DI SMP AL-QUR’AN AL-MUBAROK GENTENG - Mashuri, Imam; Rahmawati, Maria Ulfa (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
This research is behind the role of Islamic religious education teachers in succeeding the memorization activities of the Qur'an students. The type of research used is qualitative descriptive. The research was conducted at SMP Al-Qur'an Al-Mubarok Genteng. Data collection techniques through observation methods, interviews, and documentation. The results of this research are: (1) The role of Islamic religious education teacher as a mentor is very good and active through the way of mentoring and direction that aims to allow students to read the Qur'an smoothly through how to justify its short length and Tajwidnya, and to invite reading the Qur'an together. (2) The role of Islamic education teachers as motivators through communication and good attention by telling the story of the characters of Al-Qur'an and Ustadz or class-older brother who has been able to memorize the Qur'an, as well as an example of his class brothers who have been able to memorize more letters from them. (3) The role of Islamic education teachers as evaluators, i.e. the first, for the daily activities in the first process in the classical Tahfidz is to read and follow the children. Second, individually, the child advance one by one, the teacher's nature justifies reading and tajwid. Third, is the creature. (4) The inhibitory factor in improving the memorization of the Qur'an students, i.e. the education background of different students is a major factor in the teaching of Islamic education teachers to increase students ' interest in the memorization process of the Qur'an. From different educational backgrounds. Some have been able to read the Qur'an well, some are not fluent, even some do not know at all how to read. Then from the economic circumstances of parents and family environment that do not support. There are parents whose circumstances are not harmonious and there are those whose parents are not so that students do not get good attention.